Does feeding starch contribute to the risk of systemic inflammation in dairy cattle? - K.C. Krogstad; B.J. Bradford (JDS Communications, 2023)
In the high-producing dairy cow, providing an adequate supply of digestible energy is essential. One strategy to meet this need is to provide fermentable starch from cereal grains or silages like corn, barley, or wheat. Unfortunately, excess dietary starch increases the risk of rumen acidosis. Rumen acidosis challenge models using high-grain diets, particularly with wheat and barley, have demonstrated that a sudden change in starch concentration or digestibility leads to the breakdown of the rumen epithelial barrier. As a result, increases in circulating lipopolysaccharide (a marker of bacterial translocation) and acute phase proteins (APP) have been observed. Feeding increasing amounts of starch in chronic feeding studies does not appear to consistently modulate inflammation in early-lactation cows that already experience inflammation. In mid- and late-lactation cows, increasing starch above 30% may increase APP, but the response is inconsistent and has not been investigated using different grains or differently processed starch sources. Abomasal starch infusion experiments indicate that increasing the intestinal starch supply consistently reduces fecal pH but does not lead to an APP response or changes in gut integrity. Increasing intestinal starch supply increases fecal butyrate concentrations, and butyrate has had positive effects on gut health and integrity in other species and experimental models. More chronic feeding experiments are needed to investigate how starch concentrations, sources, processing methods, and interactions affect inflammation and gut integrity. There is a paucity of data investigating the role that carbohydrate concentrations and sources play on ruminant hindgut health, integrity, function, structure, or microbiome. Currently, data indicate that feeding diets with less than 30% starch to lactating dairy cows does not contribute to systemic inflammation.